2002
DOI: 10.1002/1521-4095(20020116)14:2<161::aid-adma161>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Molecules with Metallic Quantum Wires

Abstract: Can you imagine how to detect a single molecule? Techniques, such as fluorescent spectroscopy and scanning probe microscopy have become available for us to probe single molecules. Described in this article is a simple approach based on atomically thin metallic wires. The interactions of even a single molecule with the wire may cause a large change in the conductance and mechanical properties of the wire and can thus be used to detect single molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…In addition, sensors based on polyaniline nanofiber networks display improved sensitivity and stability due to their high surface areas [159]. 3.7.1.3 Metallic-Nanowire-Based Sensing Like semiconductor nanowires, so-called metal quantum wires (extremely small metal nanowires formed by a few metal atoms) can be used to detect very subtle changes in the chemical environment [171]. Adsorption of chemical species scatters the metallic bonded electrons in the quantum wires, decreasing the quantized conductance to a fractional value [172,173].…”
Section: Carbon-nanotube-based Sensingsupporting
confidence: 93%
“…In addition, sensors based on polyaniline nanofiber networks display improved sensitivity and stability due to their high surface areas [159]. 3.7.1.3 Metallic-Nanowire-Based Sensing Like semiconductor nanowires, so-called metal quantum wires (extremely small metal nanowires formed by a few metal atoms) can be used to detect very subtle changes in the chemical environment [171]. Adsorption of chemical species scatters the metallic bonded electrons in the quantum wires, decreasing the quantized conductance to a fractional value [172,173].…”
Section: Carbon-nanotube-based Sensingsupporting
confidence: 93%
“…Tao and co-workers have demonstrated that the conductance of atomically thin gold nanowires can be modulated by adsorption of molecules and solvent anions. 15,30,31 This is in agreement with our findings that the electronic structure of the gold nanowire changes greatly when it is complexed by thiolate or RSϪAuϪSR ligands. A more direct comparison with experiment here would require computing electronic conductance through the thiolated gold nanowires, which is planned for the future.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Tao and co-workers found that the Au quantum wires elongate after adsorption of molecules. 15 This observation also agrees with our findings. For example, we found that the optimal repeating length for the bare vertex-sharing icosahedral wire is 10.5 Å, while that for the corresponding thiolated Au wire is elongated to 11.3 Å.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Size-dependent intrinsic properties of nanomaterials are advantageous for some applications, e.g., chemiresistive sensing [4,[20][21][22][23][24][25][26][27]. However, these properties cause crucial deviations in the NWs behavior as electrodes from that of classical metal electrodes.…”
Section: Introductionmentioning
confidence: 99%